Nutritional profiling, phytochemical screening, cytotoxicity, and antioxidant content analysis for different crude extracts of Ulva lactuca from coast of Bangladesh - S.M. Bokhtiar; D. Sarker; Alima Akter; M.A. Salam; K.U. Ahmed; M.M. Anwar; M.F. Hossain; M. Ahmed; M.S. Bhuiyan; R.A. Kanta; A.K.M. Asaduzzaman; Khondoker Shahin Ahmed; et al. (Future Foods)
This current investigation assessed the proximate composition, mineral contents, phytochemicals, cytotoxicity and antioxidant activity of Ulva lactuca (UL). Five crude extracts of UL like 100% water (CE1), 50% water+50% ethanol (CE2), 50% water+50% methanol (CE3), 100% ethanol (CE4) and 100% methanol (CE5) were used to screen out the cytotoxicity, phytochemicals and antioxidant activity. DPPH, ABTS, phosphomolybdenum, reducing power, and nitric oxide scavenging activity was determined by in-vitro methods. Cytotoxicity of extracts was assayed using brine shrimp. Results indicated that powder of UL contains a comparable amount of proximate and mineral content. Phytochemical screening, Fourier transform infrared (FT-IR) and High-performance liquid chromatography (HPLC) analysis confirmed the presence of different secondary metabolites, functional groups and polyphenols. The CE1 showed highest phenolic content at 51.87 mg of GA/g and flavonoid content at 49.18 mg of quercetin/g, followed by CE2, CE3, CE4 and CE5. Regarding antioxidants, CE1 exhibited the highest antioxidant activity as evaluated by DPPH (75.62%), ABTS (57.67%), Phosphomolybdenum (124.58 mg of AAE/g), Reducing power (52.34 mg AAE/g), and NO scavenging (41.87%) assays. Cytotoxicity was found to be present in a dose-dependent manner. These results indicated that dried powder and extracts of UL contain macro-micro nutrients, and diversified phytochemicals with potential antioxidant activity.